(untitled) (Malay Literature, 2014)
A line of thought exists and develops from the socio-political and cultural atmosphere, apart from the writer’s level of public and individual awareness. Beginning with the call for "literature for society" by ASAS’50, the following decades saw more variety in literary trends, although, on the whole, established writers still remained committed to use literature as a means for raising awareness and channelling social criticism, while at the same time using it to present the ideal to which the writer aspires. In the cultural and political context of Singapore, there are three lines of thought. The first is a kind of foregrounding, in which the writer makes a universal observation of humankind and/or describes the condition of the Malay community with all its challenges and problems, touching on issues that have a basis in history or current realism. The second is the tendency to offer alternatives or echo moral messages that call for people to be more spiritual and more ethical in this life, without making a concrete link to the communal life or the structures and systems that underlie the society and nation. The third is a kind of escapism, indicated by a domestication of thought or "popularization" of literature following the dictates of a market in which light reading and entertainment-type reading materials are what sells. In Singapore today, writing is becoming more varied. What is to be observed is how literature has become the vehicle for refuting dominant ideas, apart from becoming the ground for competing ideas as writers present what they feel is the best idea in the interest of society. The challenge for developing an effective literary culture is ensuring that literary works have a clear social vision, employing good techniques and language skills, while at the same time building a grounded, people-oriented literature. This discussion will analyse the obstacles that complicate the literary culture of the Malay literature of Singapore as it aims to achieve all this. Keywords: modern literature, Singapore Malay, political culture, humanity, conflicting ideas